2023
DOI: 10.1101/2023.06.21.545928
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Separation-of-function mutants reveal the NF-κB-independent involvement of IκBα in the regulation of stem cell and oncogenic programs

Abstract: We previously demonstrated that the NF-κB inhibitor IκBα binds the chromatin together with PRC2 to regulate a subset of developmental- and stem cell-related genes. This alternative function has been elusive in both physiological and disease conditions because of the predominant role of IκBα as a negative regulator of NF-κB. We here uniquely characterize specific residues of IκBα that allow the generation of separation-of-function (SOF) mutants that are defective for either NF-κB-related (SOFΔNF-κB) or chromati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Similarly, we found that the same IκBα ΔNF-κB mutant is able to restore differentiation capacity in intestinal cells (Álvarez-Villanueva et al 2023). The role of NF-κB in mESC differentiation and pluripotency has been previously explored, and while several reports suggest that NF-κB activity correlates with differentiation and loss of pluripotency (Torres and Watt 2008), others claim that NF-κB inhibition correlates with a decrease in pluripotency gene expression (Armstrong et al 2006).…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…Similarly, we found that the same IκBα ΔNF-κB mutant is able to restore differentiation capacity in intestinal cells (Álvarez-Villanueva et al 2023). The role of NF-κB in mESC differentiation and pluripotency has been previously explored, and while several reports suggest that NF-κB activity correlates with differentiation and loss of pluripotency (Torres and Watt 2008), others claim that NF-κB inhibition correlates with a decrease in pluripotency gene expression (Armstrong et al 2006).…”
Section: Discussionmentioning
confidence: 52%
“…Disentangling the chromatin-related function of IκBα from its canonical role as an inhibitor of NF-κB has been challenging, making it difficult to determine its truly biological significance. To tackle this challenge, we engineered separation-of-function (SOF) mutants of IκBα, as detailed in 44 , by identifying specific residues that are essential for binding either NF-κB elements or histones. Interestingly, we have shown that only the histone-binding proficient IκBα mutant (IκBα ΔNF-κB ), which lacks the ability to bind to NF-κB, has the capability to reverse the stabilization of the ground state observed in IκBα-KO mESCs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations